IMPROVING TEACHER CREATIVITY THROUGH THE DEVELOPMENT OF SERVANT LEADERSHIP AND SELF EFFICACY OF TEACHERS AT MAN THROUGHOUT BOGOR REGENCY - Harjanto, Sutji; Sumardi, Sumardi; Ningtyas, Dwi Ari Lita Nugroho (UNIVERSITAS PAKUAN, 2021)
This research uses a correlational research and SITOREM analysis which consists of two independent variables, namely Serving Leadership and Self-Efficacy and one variable that is tied to Teacher Creativity. This research was conducted at MA Negeri in Bogor Regency in 2021, with a research population of 147 and there are 108 samples selected using proportional random sampling. The method used in this research is survey and data analysis techniques, with statistical statistics and simple linier regression and multiple linier regression. The research result, namely: first, there is a significant positive relationship between the variable serving leadership (X1 and teacher creativity (Y) in the form of the regression equation Å¶= 65,167 + 0,504 X1 and the validity is ry1 = 0,511 and the coefficient of determination r2y1 = 0,261. Second, there is a significant positive relationship between sel efficacy (X2) and teacher creativity (Y) with regression of the equation form Å¶= 62,883 + 0,482 X2 and the path coefficient ry2 = 0,584 and the coefficient of determination r2y2 = 0,342. Third, there is a positive and significant relationship between the serving leadership variable (X1 and self efficacy (X2) together with teacher creativity (Y) expressed in the form of regression equation Å¶= 39,904 + 0,305 X1 + 0,366 X2 with the subordinate coefficient ry12 = 0,646 and the coefficient of determination r2y12 = 0,417. Based on these things, it can be argued that teacher creativity can be increased throught increased serving leadership and self efficacy.